A fine balance? Unwrapping the coexistence of projects and non-projects in the core of the organization. Issue 3 (19th November 2019) - Nesheim, Torstein
Abstract : Purpose: The purpose of this paper is to extend the understanding of projects in permanent organizations. Previous research has captured organizational contexts where either a project logic dominates or projects support recurrent, ongoing operations. Through a case study, the author shows how projects and non-projects coexist over time in the core of the organization in a balanced manner, addressing the specific tensions in such an organization. Design/methodology/approach: The author has undertaken a case study of the Norwegian Petroleum Directorate. The analysis is based on several types of data: internal reports, descriptions of structure and roles, internal handbooks and other documents from the period 1998–2018; interviews with ten persons in different roles in the organization; and a survey of 190 employees and middle managers (response rate: 84 percent). Findings: The author finds that the balance of projects and non-project work, work units and rationale has been an institutional and stabile characteristic, rather than a transitory state of a Norwegian state directorate. It is also found that two types of products or set of tasks are reflected in two types of work groups: long-term work groups and project work groups. There is a subjective element regarding whether a new task should be integrated into an existing long-term unit or serve as the basis of creating a new project. The analysis of work organization, leadership and employee perceptions has revealed a number of similarities and differences between the two work contexts: the long-term work groups and the projects. The balance of projects and non-projects is maintained through shared beliefs and the process of allocation of personnel. This balance is threatened through actual practice in the organization. Research limitations/implications: A case study does not allow for statistical generalizations. The implication of the study is the revelation of a potential research gap "between" a project-based organization (PBO), on the one hand, and a project-supported organization (PSO), on the other hand. Practical implications: For organizations that combine projects and non-projects in the core, the paper could contribute to the understanding of tensions and the way to handle them, and provide inspiration regarding mechanisms for resource allocation. Originality/value: This paper identifies and empirically describes an organization where both projects and non-projects are of great importance in the core activities of the firm, thus filling a "gap" between the PBO and PSO. A number of aspects of this organization are analyzed, including how the balance of the two logics has been maintained over the two decades. The study could provide the basis for a number of research questions on the coexistence of and tensions between projects and non-projects in the core of an organization.